The Influence of Climate Variation on Abiotic Plant Stress: A Review - Ngasoh, F. G.; Jandong, E. A.; Dauda, P. A.; Ismaila, R. (International Journal of Environment, Agriculture and Biotechnology, 2019)
The increase in the carbon-dioxide (CO2) present in the atmosphere as a result of human activities affects the ambient temperature, and rainfall pattern in terms of season, duration, intensity of sunshine, increased drought periods, waterlogging, and increased evapotranspiration. This influence negatively the development, yield and quality of the plants grown under this condition. The quests to produce stress tolerant/resistant plants and increase crop productivity have led to the study of plant stresses, their response to different stress type and stress management procedures in plants. This paper has discussed in details the different abiotic stressors in plants and how they are being influenced by climate variation, the response of these plants to different abiotic stresses or a combination of stresses, and its management.